2005
DOI: 10.1097/01.prs.0000191181.73298.b3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in Septorhinoplasty? A Prospective, Randomized Study

Abstract: The authors' results would suggest that a single dose of antibiotics administered preoperatively in endonasal septorhinoplasty with autologous cartilage grafting is sufficient for prophylaxis of postoperative infections, thus eliminating the costs for postoperative antibiotics and the management of their side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 24 publications
1
67
2
2
Order By: Relevance
“…Studies of cleancontaminated head and neck procedures found no difference in efficacy between regimens of 24 hours and longer regimens of three, five, or seven days. [499][500][501]505,507,512,524,[531][532][533][534] Limited data exist on single-dose prophylaxis in these procedures.…”
Section: Head and Neck Proceduresmentioning
confidence: 98%
“…Studies of cleancontaminated head and neck procedures found no difference in efficacy between regimens of 24 hours and longer regimens of three, five, or seven days. [499][500][501]505,507,512,524,[531][532][533][534] Limited data exist on single-dose prophylaxis in these procedures.…”
Section: Head and Neck Proceduresmentioning
confidence: 98%
“…Bacteremia which occurs during septoplasty is always transient and generally does not lead to severe outcomes [14,15]. Nevertheless, serious complications, such as sepsis, toxic shock syndrome, staphylococcal endocarditis, meningitis, cavernous sinus thrombosis, or even brain abscess formation have been reported [16][17][18][19][20][21]. Usually these infections are seen in at-risk patients, such as those with cardiac diseases, immunodeficiency, and immunocompromised diseases [22,23].…”
Section: Discussionmentioning
confidence: 95%
“…Empfohlen wurde die antibiotische Prophylaxe nicht bei Septumoperatio− nen, eventuell bei Osteotomien und generell bei Transplantatio− nen [73]. In einer prospektiven Studie konnte vor kurzem gezeigt werden, dass auch bei Knorpeltransplantationen eine einwöchi− ge antibiotische Prophylaxe im Vergleich zu einer intraoperati− ven einmaligen Gabe die Infektionsrate nicht senken konnte, da− für aber mit erheblich mehr Nebenwirkungen und gesteigerten Behandlungskosten einherging [74]. Eine intraoperative antibio− tische single−shot Prophylaxe sei deshalb eventuell, eine post− operative Prophylaxe dagegen nicht indiziert.…”
Section: Antibiotische Prophylaxeunclassified
“…Dort, wo dies dennoch möglich wäre, erscheint eine Studie aufgrund einer begrenzten klini− schen Relevanz nicht immer gerechtfertigt. Einige Studien erfül− len die Anforderungen des Evidenzlevels 1b oder 1c [74,78,126,147]. Die gewonnenen Ergebnisse dieser Studien sagen jedoch zum Beispiel lediglich aus, dass der klinische Unterschied zwi− schen einer perforierenden oder kontinuierlichen Osteotomie nicht signifikant ist [147], Kortikosteroide die postoperative Schwellung lediglich 2 Tage reduzieren, ohne Einfluss auf den weiteren Verlauf [81], die antibiotische single−shot Prophylaxe einer länger dauernden Antiobiotikagabe bei Knorpeltransplan− tationen nicht unterlegen ist [74], oder nicht abgewinkelte, sa− gittal verlaufende paramediane Osteotomien im Vergleich zu 158 abgewinkelten Osteotomien am Präparat wesentlich häufi− ger zu einer unerwünschten Lateralisation der kranialen Anteile des Os nasale führen [126].…”
Section: Evidenzunclassified